Effect of Phospholipase A1-Catalyzed Degumming on Oryzanol, Tocopherols, and Tocotrienols of Dewaxed Rice Bran Oil - Sun Xiaoyang; Tian Shaojun; Zhang Lifen; Xie Jianchun (Journal of Chemistry)
The effect of phospholipase A1-catalyzed degumming on the phosphorus content, the retention rate of oryzanol, and total tocopherols and tocotrienols of dewaxed rice bran oil was investigated with comparison to water degumming and citric acid degumming. The fatty acid composition of dewaxed rice bran oil was also studied by gas chromatography. The phosphorus content of dewaxed rice bran oil after phospholipase A1-catalyzed degumming could be decreased from 332.5 mg·kg−1 to 9.3 mg·kg−1 with the citric acid dosage of 0.10%, high shearing rate of 23000 rpm, chelation time of 60 min, NaOH dosage of 1.5 mole equivalent to the amount of citric acid, reaction temperature of 50°C, and total water dosage of 2.5%, while the phosphorus content of dewaxed rice bran oil after water and acid degumming was 120.5 mg·kg−1 and 66.4 mg·kg−1, respectively. The retention rate of oryzanol and total tocopherols and tocotrienols was 97.58% and 96.81% for phospholipase A1-catalyzed degumming, 91.44% and 85.98% for water degumming, and 92.85% and 87.75% for acid degumming. There was no obvious change in fatty acid composition. The results indicated that phospholipase A1-catalyzed degumming was an effective method since it could decrease the phosphorus content to the required level and provide high retention rate of oryzanol and total content of tocopherols and tocotrienols without obvious change of fatty acid composition.